Impact of Exercise and a Complex Environment on Hippocampal Dendritic Morphology, Bdnf Gene Expression, and DNA Methylation in Male Rat Pups Neonatally Exposed to Alcohol - Boschen, K.E. (Dev Neurobiol, 2016)
Alcohol exposure in utero can result in Fetal Alcohol Spectrums Disorders (FASD). Measures of hippocampal neuroplasticity, including long-term potentiation, synaptic and dendritic organization, and adult neurogenesis, are consistently disrupted in rodent models of FASD. The current study investigated whether third trimester-equivalent binge-like alcohol exposure (AE) [postnatal days (PD) 4–9] affects dendritic morphology of immature dentate gyrus granule cells, and brain-derived neurotrophic factor (Bdnf) gene expression and DNA methylation in hippocampal tissue in adult male rats. To understand immediate impact of alcohol, DNA methylation was measured in the PD10 hippocampus. In addition, two behavioral interventions, wheel running (WR) and environmental complexity (EC), were utilized as rehabilitative therapies for alcohol-induced deficits. AE significantly decreased dendritic complexity of the immature neurons, demonstrating the long-lasting impact of neonatal alcohol exposure on dendritic morphology of immature neurons in the hippocampus. Both housing conditions robustly enhanced dendritic complexity in the AE animals. While Bdnf exon I DNA methylation was lower in the AE and sham-intubated animals compared with suckle controls on PD10, alterations to Bdnf DNA methylation and gene expression levels were not present at PD72. In control animals, exercise, but not exercise followed by housing in EC, resulted in higher levels of hippocampal Bdnf gene expression and lower DNA methylation. These studies demonstrate the long-lasting negative impact of developmental alcohol exposure on hippocampal dendritic morphology and support the implementation of exercise and complex environments as therapeutic interventions for individuals with FASD.